1998
DOI: 10.1073/pnas.95.25.15008
|View full text |Cite
|
Sign up to set email alerts
|

Memory fields of neurons in the primate prefrontal cortex

Abstract: Many prefrontal (PF) neurons convey information about both an object's identity (what) and its location (where). To explore how they represent conjunctions of what and where, we explored the receptive fields of their mnemonic activity (i.e., their ''memory fields'') by requiring monkeys to remember both an object and its location at many positions throughout a wide portion of central vision. Many PF neurons conveyed object information and had highly localized memory fields that emphasized the contralateral, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
162
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(183 citation statements)
references
References 50 publications
18
162
2
1
Order By: Relevance
“…Although there is strong evidence of this area's involvement in working memory tasks (Goldman-Rakic, 1987;Funahashi et al, 1989;Owen et al, 1996;Braver et al, 1997;Rainer et al, 1998), some have suggested that the basic role of DLPFC is to maintain an abstract representation of the rules of a task (Miller et al, 2002;Derrfuss et al, 2004) and to select responses (Rowe et al, 2000). Our results suggest some degree of functional subdivision within DLPFC as the maps do not completely cover the posterior DLPFC region activated by our task (Figs.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Although there is strong evidence of this area's involvement in working memory tasks (Goldman-Rakic, 1987;Funahashi et al, 1989;Owen et al, 1996;Braver et al, 1997;Rainer et al, 1998), some have suggested that the basic role of DLPFC is to maintain an abstract representation of the rules of a task (Miller et al, 2002;Derrfuss et al, 2004) and to select responses (Rowe et al, 2000). Our results suggest some degree of functional subdivision within DLPFC as the maps do not completely cover the posterior DLPFC region activated by our task (Figs.…”
Section: Discussioncontrasting
confidence: 56%
“…There are several reasons why maps in higherlevel areas are more difficult to accurately and reliably measure. First, in areas such as DLPFC, only a subset of neurons display spatial preference (Funahashi et al, 1989;Rainer et al, 1998). Second, task-related activity that is non-spatially selective could cause fluctuations in blood oxygenation level dependent (BOLD) signals that actively reduce the significance of the correlation with stimulus location; this effect could differ between hemispheres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the cellular level, learning-dependent neuronal activity has been found in the premotor cortex (16), the supplementary motor cortex (17,18), the supplementary eye field (19), the prefrontal cortex (20,21), and the somatosensory areas (22). With respect to the primary motor cortex, the study of Wise et al (23) also has shown learning at the level of the cells of this area.…”
Section: Discussionmentioning
confidence: 79%